Above‐ and Belowground Development of a Fast‐Growing Willow Planted in Acid‐Generating Mine Technosol. Issue 6 (1st November 2017) - Guittonny‐Larchevêque, M.; Lortie, S.
Abstract : Surface metal mining produces large volumes of waste rocks. If they contain sulfide minerals, these rocks can generate a flow of acidic water from the mining site, known as acid mine drainage (AMD), which increases trace metals availability for plant roots. Adequate root development is crucial to decreasing planting stress and improving phytoremediation with woody species. However, techniques to improve revegetation success rarely take into account root development. An experiment was conducted at a gold mine in Quebec, Canada, to evaluate the establishment ability over 3 yr of a fast‐growing willow ( Salix miyabeana Sx64) planted in acid‐generating waste rocks. The main objective was to study root development in the soil profile and trace element accumulation in leaves among substrates varying in thickness (0, 20, and 40 cm of soil) and composition (organic carbon [OC] and alkaline AMD treatment sludge). Trees directly planted in waste rocks survived well (69%) but had the lowest productivity (lowest growth in height and diameter, aerial biomass, total leaf area, and root‐system size). By contrast, the treatment richer in OC showed the greatest aerial biomass and total leaf area the first year; the thicker treatment resulted in the greatest growth in height and diameter, aboveground biomass, and root‐system size in both the first and third years. Willow root development was restricted to soil layers during the first year, but this restriction was overcome in the third year after planting. Willow accumulation factors in leaves were below one for all investigated trace metals except for zinc (Zn), cadmium (Cd), and strontium. For Cd and Zn, concentrations increased with time in willow foliage, decreasing the potential of this willow species use for phytostabilization, despite its ability to rapidly develop extensive root systems in the mine Technosol. Core Ideas: Salix miyabeana grew roots extensively in shale waste rocks, even if AMD generating. Root development in waste rocks was delayed at least 1 yr under soil layers. A soil layer of 40 cm maximized root system size after 3 yr. Soil layer thickness rather than organic matter content determined sustained productivity. Salix miyabeana accumulated Cd and Zn in foliage over time, especially with soil layers.